A Cholesterol Containing pH‐Sensitive Bistable [2]Rotaxane. Issue 27 (September 2015) - Berg, Martin; Nozinovic, Senada; Engeser, Marianne; Lützen, Arne
Abstract: A non‐symmetrical pH‐sensitive bistable [2]rotaxane that bears a cholesterol unit and a tetraphenylmethane group as stopper groups was designed and synthesized in 18 steps. The successful formation of the rotaxane was proven by NMR spectroscopy and MS/MS. Besides a permanent cationic alkylated triazolium unit, the axle contains a secondary amine that can act as a second pH‐sensitive binding site for a crown ether. Depending on the protonation state of this amine function, the crown ether reversibly changes its position by moving between the two binding sites along the axle, as revealed by NMR spectroscopy. Abstract : A pH‐sensitive bistable [2]rotaxane was synthesized and characterized by NMR spectroscopy and MS/MS. Besides an alkylated triazolium ion, the axle contains a secondary amine that acts as a second pH‐sensitive binding site for a crown ether. Depending on the protonation state of this amine function, the crown ether reversibly changes its position by moving between two binding sites on the axles.